Network Selection in Heterogeneous Wireless Networks: Evolution with Incomplete Information - Kun Zhu; Niyato, Dusit; Ping Wang (2010 IEEE Wireless Communication and Networking Conference, 2010)
Enabling users to connect to the best available network, dynamic network selection scheme is important for satisfying various quality of service (QoS) requirements, achieving seamless mobility and load balancing in heterogeneous wireless networks. In this paper, we formulate the network selection problem in heterogeneous wireless networks with incomplete information as a Bayesian game. In general, the preference (i.e., utility) of a mobile user is private information. Therefore, each user has to make the decision of network selection optimally given only the partial information of the preferences of other users. To study the dynamics of such network selection, the Bayesian best response dynamics and aggregate best response dynamics are applied. Bayesian Nash equilibrium is considered to be the solution of this game, and there is a one-to-one mapping between the Bayesian Nash equilibrium and the equilibrium distribution of the aggregate dynamics. The numerical results show the convergence of the aggregate best response dynamics for this Bayesian network selection game. This result ensures that even with incomplete information, the equilibrium of network selection decisions of mobile users can be reached.